Explaining the Understanding of Elderly Patients with Type 2 Diabetes Regarding Information Therapy Related to Self-care: A Qualitative Study - Masoud Koorki; Alireza Isfandyari–Moghaddam; Atefeh Zarei; Sahar Khoshravesh; Erfan Ayubi (پزشکی بالینی ابن سینا)
Background and Objective: Information therapy is one of the new methods of providing health-related information to patients. This method plays an important role in empowering patients to make informed health decisions and participate in the recovery process. In this regard, the present study was conducted to explain the understanding of elderly people with type 2 diabetes regarding information therapy related to self-care. Materials and Methods: This study was carried out qualitatively using the content analysis method on 18 patients with type 2 diabetes referred to some specialized diabetes centers in Hamadan City in 2024. Participants were selected based on purposeful sampling method and content saturation with maximum diversity based on gender, education level, marital status, employment status, and duration of diabetes among patients eligible for the study. A semi-structured, in-depth personal interview method was used for data collection. All interviews were recorded, transcribed, and then analyzed using MAXQDA 2020 software. Results: After data analysis, three categories and thirteen subcategories were extracted in relation to the theme of diabetes control and management. The obtained categories included promoting self-care behaviors, increasing individuals' motivation to perform self-care behaviors, and accessing information therapy communication channels. Subcategories included paying attention to physical, psychological, social, and spiritual self-care; boosting awareness; improving attitude; controlling disease and its complications; reducing costs and making better decisions; and interpersonal media, traditional media, digital media, and social networks. Conclusion: According to the results, it seems that information therapy is one of the methods of increasing individuals' motivation to perform self-care behaviors and promoting self-care behaviors. Ultimately, it may assist elderly patients in controlling and managing type 2 diabetes.